Association between gaseous pollutants and emergency ambulance dispatches for asthma in Chengdu, China: a time-stratified case-crossover study - Jianyu Chen; Xianyan Jiang; Chunli Shi; Ruicong Liu; Rong Lu; Li Zhang (Komiyama Printing Co. Ltd, 2019)
Abstract Objectives The association between concentrations of sulfur dioxide (SO2), nitrogen dioxide (NO2), carbon monoxide (CO), ozone (O3), and emergency ambulance dispatches (EADs) for asthma was explored in the central Sichuan Basin of southwestern China for the first time. Methods EADs for asthma were collected from the Chengdu First-Aid Command Center. Pollutant concentrations were collected from 24 municipal environmental monitoring centers and including SO2, NO2, CO, daily 8-h mean concentrations of O3 (O3-8 h), and particulate matter less than 2.5 μm in aerodynamic diameter (PM2.5). The climatic data were collected from the Chengdu Municipal Meteorological Bureau. All data were collected from years spanning 2013-2017. A time-stratified case-crossover design was used to analyze the data. Results After controlling for temperature, relative humidity, and atmospheric pressure, IQR increases in SO2 (13 μg/m3), NO2 (17 μg/m3), and CO (498 μg/m3) were associated with 18.8%, 11.5%, and 3.1% increases in EADs for asthma, respectively. The associations were strongest for EADs and SO2, NO2, and CO levels with 3-, 5-, and 1-day lags, respectively. Conclusions This study provides additional data to the limited body of literature for potential health risks arising from ambient gaseous pollutants. The results of the study suggest that increased concentrations of SO2, NO2, and CO were positively associated with emergency ambulance dispatches for asthma in Chengdu, China. Further studies are needed to investigate the effects of individual air pollutants on asthma.